Loss minimisation using islanding technique for district of Klang, Malaysia - Shaibon, H.; Mohd Zin, A.A.; Lim, Y.S.; Lo, K.H. (IEEE, 1995)
Distribution system loss reduction has been grossly neglected by most electricity utilities even though it contributes to no less than 75 percent of the total system losses. Existing methods of loss reduction involve enormous capital cost and extensive rehabilitation to the existing distribution reticulation and are hence not very practical, compounded with the problem of coping with the high and dynamic load growth in most developing countries. The paper looks into techniques of selecting and operating the distribution system,with minimum or no physical change in the present distribution reticulation to reduce losses. It proposes that the existing distribution network be operated in 'island groups' by paralleling selected feeders into an island.